Diasporas, weddings and trajectories of ethnicity - Heng, Terence, 1978- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"In an age of increasingly fragmented migration, consumption and globalisation, how do diasporic individuals navigate their ethnic identities? Diasporas, Weddings and Trajectories of Ethnicity investigates the ways that Chinese Singaporeans shape their Chineseness through wedding rituals and artefacts. Proposing a framework of ethnic identity as a journey, this book will Interrogate the processes underlying diasporic ethncity-making through weddings Offer new concepts of transdiasporic space, ethnic tastes and aesthetic dissonance Explore the intersections between commercialism, ethnicity and socio-economic divides Map the micro-social ramifications of ethnic and racial policy in Singapore As a former professional wedding photographer, Terence Heng brings a sociological lens to the scripted and spontaneous arena of social interactions that is the wedding day. By combining ethnographic observation, photography and poetry, Heng reveals the many decisions and demands that underscore Singaporean Chinese weddings, offering novel insights into the roles of the bridal couple, their social networks, and the wedding industry"--
Introduction -- Reconceptualising Diasporic Space as Transdiasporic Space -- Configuring Transdiasporic Ethnicity, Ethnic Lifestyles and Ethnic Tastes -- Weddings as Sites of Ethnicity-Making -- Observation, Photography and Poetry -- A Methodological Framework of Creative Practice and Social Research -- A Visual Introduction to Singapore and Singaporean Chineseness -- Taste Performances: Making Ethnic Lifestyles Interactive -- Ethnic Taste and Aesthetic Dissonance -- Ethnic Taste, Everyday Commercial Activities and the Commercially Dominant Wedding Aesthetic -- Conclusion: Aesthetic Dissonance, Ethnic Hybridity and Economic Life-Paths -- Epilogue: Look on My Hands and See it There.
OCLC-licensed vendor bibliographic record.
Keywords: Chinese -- Singapore -- Social life and customs; Marriage customs and rites -- Singapore; Chinese -- Marriage customs and rites -- Singapore; SOCIAL SCIENCE / Sociology / General